Bridging the Gap: The Role of Distance and Online Education in Enhancing Skill Development and Employability of Divyang Persons in India - Jain, Dr. Trilok Kumar; Manisha Jain (Journal of Advanced Research in Operational and Marketing Management, 2025)
Purpose: This study investigates the transformative impact of distance and online education on the skill development and employability of Divyangs (persons with disabilities) in India. While these educational modalities offer unprecedented access, significant barriers remain in translating education into sustainable employment. This research aims to identify the key enablers and obstacles within this ecosystem and propose a strategic framework for improvement. Design/Methodology/Approach: A qualitative, exploratory research design was employed. Data was collected through 25 in-depth, semi-structured interviews with Divyang students and graduates from various Indian distance education institutions, supplemented by focus group discussions with 10 experts from academia, disability NGOs, and corporate HR. Findings: The findings reveal that online education significantly enhances access to education and the development of digital and self-management skills. However, a critical "skills-employability gap" persists, driven by a lack of tailored career services, inadequate industry-specific skill training, persistent societal and workplace stigma, and insufficient accessibility features in many online platforms. Research Limitations/Implications: The study's qualitative approach provides depth but limits generalisability. Future research should include quantitative surveys across broader geographical regions. Practical Implications: The findings urge educational institutions to integrate robust, personalised career guidance, industry-aligned practical modules, and stronger corporate partnerships into their online offerings. Policymakers are called upon to incentivise inclusive hiring and fund assistive technology. Originality/Value: This paper moves beyond access to education, focusing on the under-researched linkage between online education and tangible employment outcomes for Divyang persons. It proposes a novel, multi-stakeholder framework to bridge the skills-employability gap, offering significant value to educators, policymakers, and employers.